URGENSI MORALITAS PENEGAK HUKUM DALAMPENYELESAIAN PERKARA PENIPUAN DAN PENGGELAPANYANG DIKUALIFIKASIKAN SEBAGAI TINDAK PIDANAPENCUCIAN UANG - M. Irwansyah (2022)
Law enforcement by Police investigators in resolving criminal cases of fraud and embezzlement which are qualified as money laundering crimes, in accordance with Pretrial decision Number: 33/Pid.Prap/2020/PN.Jkt.Sel., does not meet the provisions of the investigation and investigation mechanism as regulated in the provisions of the Regulation of the Head of the State Police of the Republic of Indonesia Number 6 of 2019 concerning Management of Criminal Investigations. This discrepancy is motivated by the lack of appreciation of law enforcement officers in implementing the morals contained in the provisions of the Regulation of the Chief of the Indonesian National Police Number 14 of 2011 concerning the Code of Ethics of the Indonesian National Police. That the lack of understanding and public awareness of the law is still low, it also affects actions that are not in accordance with applicable legal provisions, therefore the presence of this legal research is to answer these moral problems in order to become professional law enforcement officers and prioritize moral values. This can be done in several ways, namely: 1. Instilling awareness of the discipline of Polri investigators 2. Building an objective, professional work system, and prioritizing mastery of the field 3. Building a coordination work system among Polri members 4. Prioritizing the morality contained in the guidelines Police professional code of ethics 5. As well as an objective and professional monitoring system for the performance of Polri members. That the 5 (five) points are the ways and solutions in tackling legal problems in this study, so that they are in accordance with the objectives of law enforcement, namely: justice, certainty and expediency.